PENINGKATAN HASIL BELAJAR ILMU PENGETAHUAN SOSIAL MENGGUNAKAN METODE SCRAMBLE KELAS IV SEKOLAH DASAR - Unyil, Iyes; Sugiyono, Sugiyono; Kartono, Kartono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This study aims to improve teacher performance through the ability of teachers in design and implement learning that is marked by the success of teachers in improving student learning outcomes. The stages in this study are planning, implementing, observing, and reflecting. This continues to be repeated so that the research objectives are achieved. This research is collaborative, uses descriptive methods with a form of classroom action research, and is collaborative. Data collection techniq used were direct observation and question sheets and measurement techniq with data collection tools namely observation sheets. The collected data is calculated and analyzed by an average calculation. The data analysis technique used is to use an average calculation formula. The subjects of this study were the fourth grade students of Primary School 02 Sebente amounting to 25 students consisting of 17 male students and 8 female students. This research was carried out in 3 cycles with the results 1) the average ability of the teacher to plan learning, namely as follows in the first cycle 3.13, in the second cycle 3.26, in the third cycle 3.60. 2) the average ability of teachers to carry out learning as follows in the first cycle 3.01, in the second cycle 3.20, in the third cycle 3.64. 3) the average student learning outcomes are as follows, in the first cycle 55.92, in the second cycle 74.81, and in the third cycle 86.29. From the data obtained, it can be concluded that the Scramble method can improve student learning outcomes. Keywords: Improvement, Learning Outcomes, Scramble Method, Social Sciences.